Linking CSR to strategy: A practical view - Olgierd Swiatkiewicz (Foundations of Management, 2017)
The purpose of this paper is to present a basic compendium of how companies can integrate social responsibility into their strategies. The paper analyzes and synthesizes ideas and proposals based on the literature review from different fields. It proposes a practical approach that does not highlight the differences but the positive and mutual synergy of social responsibility with firm's strategy. There are many practical proposals in the literature and a lot of successful examples from business practice that show how organizations can or have made the implementation of social responsibility into their strategy to work efficiently, but their strategic, social, and environmental importance differs and is limited by many factors. The paper presents different means of connecting social responsibility with organizational strategy to make it work, which can be useful for practitioners, students, and wider public. The paper adds the praxiological or practical perspective to deal with a small but persisting organizational problem and a great social expectation, how to link efficiently social responsibility with organizational strategy into one coherent stream of purposes.
Keywords: 650; strategy; social responsibility; environmental responsibility; triple bottom line; CSR; organization; praxiological/practical approach